Transformational leadership and listening: do they listen? - Adesopo, Mabel (My University, 2024)
Transformational leadership theory suggests that leaders can inspire commitment toward collective goals by expanding employees’ interests and awareness to align with a larger shared vision, all while demonstrating consideration for individual needs. This type of approach is particularly important when trying to generate commitment to organizational change, where resistance and a lack of buy-in often thwart success. Indeed, a recent meta-analysis by Peng et al. (2021) suggests that transformational leadership is associated with higher levels of commitment to, openness to, and readiness for change, and lower levels of cynicism and resistance toward change. Like transformational leadership but situated primarily at the dyadic level, listening is also theorized to facilitate cooperation and openness to change while allowing an individual to relax their defences (Kluger & Itzchakov, 2022). Given these parallels, and the ability for listening to facilitate an awareness of and responsiveness toward individual needs in alignment with the individualized consideration component of transformational leadership, it makes sense to examine whether listening plays a role within transformational leadership. To date, very little is written about listening in its role within transformational leadership. This paper proposes to bridge that gap by undertaking a review of the literature regarding listening and transformational leadership.
Presented on April 19, 2024 at Student Research Day held at MacEwan University in Edmonton, Alberta.
Keywords: transformational leadership; listening